Repositioning the Cobb human archive: The merger of a skeletal collection and its texts. Issue 1 (7th November 2014) - Watkins, Rachel; Muller, Jennifer
ABSTRACT The W. Montague Cobb skeletal collection, mainly comprised of African Americans living in Washington, DC, before 1969, is an important collection for human biological studies of the African Diaspora. This article outlines the process of constructing an improved study sample for biocultural analysis by merging skeletal remains from the collection with their associated texts. The merging allows for the inclusion of individuals from the original series for whom we no longer have skeletons. We argue that this step is necessary to construct a data set that reflects the demographic breadth (age, ethnicity, social class) of the original collection, taking into account a substantial number of skeletons lost during storage and disuse. The mechanics of this process were informed by a critical and humanistic orientation toward human biological study built upon the following premises: (1) scientific investigation is not an objective or passive practice, nor must it be; and, (2) relevant, publically accessible human biological research requires competence with social justice issues, as well as previous and current scholarship focused on addressing those issues. This approach to sample construction engages skeletal remains as biological and social products, and enhances the social and translational implications of our research practices. Am. J. Hum. Biol. 27:41–50, 2015. © 2014 Wiley Periodicals, Inc.